Beta-Lactamases Production in Multi-drug Resistant Acinetobacter species Isolated from Different Clinical Specimens - Neupane, Mary; K.C., Sudeep; Thakur, Subash Kumar; Panta, Om Prakash; Joshi, Dev Raj; Khanal, Santosh (Tribhuvan University Journal of Microbiology, 2019)
Objectives: To determine the prevalence of Acinetobacter spp. from different clinical specimens and detect different types of β-lactamase enzymes. Methods: Different clinical samples were collected and 125 Acinetobacter spp. were isolated. Various biochemical tests were carried out to speciate the Acinetobacter spp. The antibiotic susceptibility pattern and β-lactamase enzymes like Extended spectrum β-lactamase (ESBL), Metallo β-lactamase (MBL) and AmpC β-lactamase were determined. Results: Of the total 125 isolates, the most predominant species was Acinetobacter calcoaceticus-A. baumannii (Acb) complex (80%). Highest rate of isolation of Acinetobacter species were from in-patients (neonates’ blood sample). Among all, 44.8% isolates were found to be MDR with the majority being resistant to aminoglycosides, carbapenems and fluoroquinolones but not to colistin. ESBL, MBL and AmpC beta-lactamase was detected in 43.2%, 15.2% and 1.6% of the isolates respectively. Conclusion: Acinetobacter calcoaceticus-A. baumannii complex should be considered for detection in hospitalized patients. The analysis of antibiotic susceptibility pattern and β-lactamases would be helpful to establish network surveillance in order to maintain and control the spread of these resistant strains.